2017
DOI: 10.3233/thc-161245
|View full text |Cite
|
Sign up to set email alerts
|

Variability of hemodynamic parameters using the common viscosity assumption in a computational fluid dynamics analysis of intracranial aneurysms

Abstract: Variability of hemodynamic parameters using the common viscosity assumption in a computational fluid dynamics analysis of intracranial aneurysms Takashi Abstract. BACKGROUND: In most simulations of intracranial aneurysm hemodynamics, blood is assumed to be a Newtonian fluid. However, it is a non-Newtonian fluid, and its viscosity profile differs among individuals. Therefore, the common viscosity assumption may not be valid for all patients. OBJECTIVE: This study aims to test the suitability of the common visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…They concluded that adopting a non-Newtonian viscosity model highlighted the hemodynamic differences induced by the presence of a bleb and improved the discriminant statistics in rupture prediction. Suzuki et al 36 first compared the CFD simulation results of the Newtonian viscosity model with those of actual viscosity data obtained from blood sample data of healthy volunteers. They concluded that CFD using either the common Newtonian or non-Newtonian viscosity assumption could lead to values different from those of the patient-specific viscosity model for hemodynamic parameters such as WSS.…”
Section: Limitations Of Cfd Studiesmentioning
confidence: 99%
“…They concluded that adopting a non-Newtonian viscosity model highlighted the hemodynamic differences induced by the presence of a bleb and improved the discriminant statistics in rupture prediction. Suzuki et al 36 first compared the CFD simulation results of the Newtonian viscosity model with those of actual viscosity data obtained from blood sample data of healthy volunteers. They concluded that CFD using either the common Newtonian or non-Newtonian viscosity assumption could lead to values different from those of the patient-specific viscosity model for hemodynamic parameters such as WSS.…”
Section: Limitations Of Cfd Studiesmentioning
confidence: 99%
“…[54][55][56] For this purpose, CFD simulations should account for the sensitive values of WSS, as indicated by the results of Zhou et al 15 Different non-Newtonian models produce deviations from the Newtonian assumption within similar ranges to the MKM. 4 However, due to the empirical nature of the non-Newtonian model, they are not consistent and sometimes they produce higher WSS (i.e. less sensitive results).…”
Section: Wall Shear Stressmentioning
confidence: 99%
“…Recent literature shows considerable differences in CA wall shear stress (WSS) between Newtonian and non-Newtonian models. [4][5][6] Each and every non-Newtonian model has different underlying physics. 7 However, the majority of such models are empirical correlations which represent blood as shear-thinning fluid regardless of its components.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al 19) reported a reduction in WSS at the aneurysmal bleb by CFD analysis with Casson's model in comparison with the Newtonian model, suggesting that the risk of aneurysmal rupture may be underestimated by Newtonian model calculation. Suzuki et al 20) applied two models, Casson's and Newtonian models, which differ in viscosity, for CFD analysis of unruptured cerebral aneurysms, and reported that the normalized WSS was reduced by 25% at maximum in Casson's model, suggesting the influence of viscosity on CFD analysis. In this study, we prepared Casson's model from the average shear rate-blood viscosity curve based on the actual values of 50 healthy adults, and applied it for CFD analysis for the first time.…”
Section: Cfd Analysis Using Casson's Modelmentioning
confidence: 99%